1994
DOI: 10.1111/j.1469-8137.1994.tb02984.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell differentiation and the cytoskeleton in Acetabularia

Abstract: summary In multicellular organisms, differentiation of individual cells is typically linked to the development of the whole organism. As cells acquire tissue‐specific morphologies and become functionally specialized they lose in turn a number of other functions. A free living, single celled organism, however, maintains all such functions. Compartmentalization and intracellular communication are two basic principles by which expression of specialized features is achieved within a unicell. Both in turn depend on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 78 publications
(65 reference statements)
2
24
0
Order By: Relevance
“…ADP-Glc-P mRNA specifies ADPGlc pyrophosphorylase, an enzyme involved in starch synthesis that is at least partly located in the plastids. A similar localization is expected for the actin isoform-1 mRNA, because actin microfilaments run through the entire cell (see Menzel, 1994). The distribution of tubulin mRNAs deserves some special consideration.…”
Section: Cell Polarity and The Distribution Of Mrnassupporting
confidence: 59%
See 2 more Smart Citations
“…ADP-Glc-P mRNA specifies ADPGlc pyrophosphorylase, an enzyme involved in starch synthesis that is at least partly located in the plastids. A similar localization is expected for the actin isoform-1 mRNA, because actin microfilaments run through the entire cell (see Menzel, 1994). The distribution of tubulin mRNAs deserves some special consideration.…”
Section: Cell Polarity and The Distribution Of Mrnassupporting
confidence: 59%
“…Sawitzky (1997) established that tubulin mRNAs are present in the A. acetabulum cell at all developmental ages, and in this study, we found these mRNAs to be nearly ubiquitous in all parts of the cell. However, neither microtubules nor unassembled tubulin proteins were detected during vegetative development until after meiosis (Menzel, 1994;Sawitzky, 1997). These findings suggest that tubulin mRNAs are synthesized and stored in the A. acetabulum cytoplasm long before they are actually used for synthesis of the corresponding tubulin proteins.…”
Section: Cell Polarity and The Distribution Of Mrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Many Dasycladales, however, remain uninucleate throughout much of their life cycle with a giant diploid nucleus that only divides at the onset of reproduction (Berger & Kaever, 1992). In contrast to the siphonocladous type, the cytoplasm of siphonous algae exhibits vigorous streaming, enabling transportation of transcripts across the plant (Menzel, 1987;Menzel, 1994;Mine et al, 2001). Although some siphonous algae are tiny microscopic siphons, many form large and complex seaweeds that exhibit morphological differentiation into structures that resemble the roots, stems, and leaves of land plants and even have similar functions (Chisholm et al, 1996).…”
Section: Ulvophyceaementioning
confidence: 99%
“…Transplant experiments with the giant-celled Acetabularia, conducted by Joachim Hämmerling, demonstrated that the nucleus of a cell contains the genetic information that directs cellular development, and postulated the existence of messenger RNA before its structure was determined (Hämmerling, 1953). Acetabularia, along with other giant-celled green algae (Valonia, Chara and Nitella), has also served as an experimental organism for electro-physiological research and studies of cell morphogenesis (Menzel, 1994;Mandoli, 1998;Shepherd et al, 2004;Bisson et al, 2006;Mine et al, 2008). The charophyte Mougeotia played a key role in outlining the role of phytochrome in plant development (Winands & Wagner, 1996).…”
mentioning
confidence: 99%